Can a fighter develop glass jaw? Statistical evidence from mixed martial arts (Revista de Artes Marciales Asiáticas, 2023)
This paper deals with a phenomenon in combat sports called the glass jaw or glass chin. It is the ability of a fighter to withstand punches to the jaw area without falling unconscious and thus receiving a knockout. The main objective of this paper is to investigate the possibility of developing a glass jaw over the course of a fighter's career, and whether certain fighters are more predisposed to experiencing knockouts. Utilizing data from the largest Mixed Martial Arts organization, the Ultimate Fighting Championship, spanning from 2010 to 2021, statistical models reveal that certain fighters may be more susceptible to knockouts compared to others. Conversely, it could not be shown that the probability of a future knockout loss, that is developing a glass jaw, increased with the number of knockouts received. However, there remains space for a more detailed investigation of this phenomenon. The historically debated resistance training of punches to the head area cannot be recommended. Conversely, it is advisable to observe the fighters' reactions to punches to the head in order to pick out those with a greater predisposition for a knockout. They should then be especially cautious when practicing combat sports.